The ethics of ḥayā’ in contemporary Middle Eastern Salafism: meaning, forms and functions of modesty - Belhaj, Abdessamad (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2025)
This article examines the concept of ḥayāʼ (modesty) in contemporary Salafi discourse, a topic that is often overlooked in academic studies, reducing it to a narrow understanding of shame. In relation to classical Islamic ethics present ḥayāʼ as a multidimensional virtue encompassing dignity, self-restraint, and moral responsibility, this study fills the gap by analysing how modern Salafi thinkers redefine ḥayāʼ as a preventive ethical framework central to Islamic piety and behaviour. The research aims at identifying the meanings, forms, and functions of ḥayāʼ as exemplified in five major Salafi texts from Egypt, Jordan, Lebanon, and Saudi Arabia. It employs a tripartite approach consisting of historical contextualization, close textual analysis, and ethical interpretation to establish contemporary Salafi modesty discourse within the broader Islamic moral tradition. The findings show that Salafi scholars combine classical ḥadith-based definitions with determined Sufi ethical insights to present ḥayāʼ as a comprehensive moral force. They emphasise its role in fostering God-consciousness, discouraging immoral behaviour, and nurturing disciplined conduct, thereby reinforcing both individual virtue and social order. The study demonstrates that Salafi ethics of modesty reflect a hybrid character that remains committed to tradition while adapting to contemporary Muslim contexts. As a result, this research contributes to a more nuanced understanding of Islamic ethics, particularly in clarifying the expanding role of ḥayāʼ in the Salafi discourse. It also encourages further research to assess how other Islamic schools align or differ from Salafism in their ethical views on ḥayāʼ and related virtues.